Two-Week Central Macular Thickness Reduction Rate >37% Predicts the Long-Term Efficacy of Anti-vascular Endothelial Growth Factor Treatment for Macular Edema Secondary to Retinal Vein Occlusion - Zhou, Jialin; Ma, Huafeng; Zhou, Xiyuan; Wang, Qiuyu; Li, Weihou; Luo, Shuai; Cai, Chang; Li, Zefeng; Liu, Danning (Frontiers in Medicine, 2022)
Objective: To determine if the early response assessments can predict the long-term efficacy of anti-vascular endothelial growth factor (VEGF) treatment for macular edema secondary to retinal vein occlusion (RVO-ME). Methods: A retrospective study of patients with diagnosis of RVO-ME and intravitreal anti-VEGF treatment was conducted. Clinical characteristics including age, gender, disease subtype and disease duration were recorded at baseline. The best corrected visual acuity (BCVA, logMAR), intraocular pressure (IOP), and central macular thickness (CMT) were recorded at baseline, 2 weeks, and every month (months 1-6) after injection. Further, we compared the early response assessments between the cured group (6-month CMT≤250μm) and the uncured group (6-month CMT>250μm). Results: A total of 164 eyes in 164 patients (77 male, 87 female) were included. At each post-injection time point, both BCVA and CMT are significantly decreased from baseline (all P<0.001). Spearman's test showed that 2-week CMT reduction rate after the first injection was negatively correlated with BCVA at 6 months (r= -0.359, P<0.001). Compared with the uncured group (47 cases), the cured group (117 cases) was younger (59.53±11.68 vs. 65.19±13.10 years old, P<0.01), had more BRVO patients (76.1% vs. 44.7%, P<0.01), a shorter disease duration (1.92±2.43 vs. 5.05±4.32 months, P<0.01), lower baseline CMT (527.09±154.95 vs. 768.96±287.75 μm, P<0.01), and lower baseline BCVA (0.86±0.44 vs. 1.31±0.51, P<0.01). At each post-injection time point, the cured group had lower CMT and BCVA values when compared to the uncured group (all P<0.01), and the 2-week CMT reduction rate was identified as the earliest response time to predict the long-term treatment efficacy. Moreover, ROC curve analysis indicated that a 2-week CMT reduction rate >37% yielded the best cut-off point for predicting the long-term cure of anti-VEGF treatment at 6 months (P<0.001). Multivariable logistic regression confirmed that the 2-week CMT reduction rate >37% was independently associated with the 6-month cured rate (OR=9.639, 95% Cl=1.030-90.227, P=0.047). Conclusion: Age, disease duration, baseline CMT and baseline BCVA are associated with visual outcomes at 6-month of anti-VEGF treatment for RVO-ME. The “2-week CMT reduction rate >37%” after the first injection is an independent factor to predict better long-term outcomes.